Розробка дискримінатора для дослідження флуктуацій генераторів НВЧ - Кудря, Т. К. (ХНУРЕ, 2024)
This work is devoted to the development of a discriminator design for studying fluctuations of microwave generators. Improving designs for the study of radio signals, their noise characteristics, and the like, is a very urgent task even in present time. This report examines the concept discriminator, its models, designs and purposes of various resonators and a description of the finished device. The developed frequency discriminator can be used in both high frequency and low-frequency systems, such as automatic frequency tuning systems, measurement systems and radio signal research, as well as for certain scientific research.
Keywords: розробка дискримінатора; дослідження флуктуацій генераторів НВЧ